2002
DOI: 10.1038/sj.cgt.7700540
|View full text |Cite
|
Sign up to set email alerts
|

Principles of tumor immunosurveillance and implications for immunotherapy

Abstract: Although antigen loss variants, major histocompatibility ( MHC ) class I down -regulation, or the expression of inhibitory molecules may explain the failure of immunosurveillance against some tumors, this seems not to apply for many other solid peripheral or lymphohematopoietic tumors. Why then is immunosurveillance so ineffective and can it be improved? This review focuses on one important aspect of tumor immunity, namely the relevance of antigen dose and localization. Immune responses in vivo are induced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 122 publications
(125 reference statements)
1
62
0
1
Order By: Relevance
“…T cells play an important role in immunological surveillance against cancer cells as well as in tumor destruction (20). Successful identification of a number of tumor Ags from both human and murine melanomas has allowed the development of Ag-specific cancer vaccines (21).…”
Section: Discussionmentioning
confidence: 99%
“…T cells play an important role in immunological surveillance against cancer cells as well as in tumor destruction (20). Successful identification of a number of tumor Ags from both human and murine melanomas has allowed the development of Ag-specific cancer vaccines (21).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies (16) suggest that high Ag doses in SLOs lead to the development of T cell tolerance. Accordingly, we examined the susceptibility to cell death of Ag-specific CD8 T cells in the LNs and spleen upon TCR re-engagement with high doses of Ag: we used annexin V staining to analyze the death rate and found that many more CD8 cells restimulated with EG7 died within 24 h (39 and 30% of the CD8 cells isolated, respectively, from the LNs and spleen) than did those restimulated with EL-4 (12 and 16%) (Fig.…”
Section: Ag Distribution Determined Outcome: Effector Functions or Cementioning
confidence: 94%
“…Furthermore, diffusely invading systemic tumors delete CTLs. Thus, it is the Ag dose in the SLOs that determines whether T cells remain ignorant, are activated, or become tolerized (15,16). Precise definitions of the kinetics of CD8 antitumor activation, proliferation, migration, and differentiation are crucial in improving the efficiency of tumor rejection.…”
mentioning
confidence: 99%
“…Antitumor cytotoxic T-lymphocytes (CTLs) are central to immunotherapeutic anticancer strategies (1)(2)(3)(4)(5). Tumorspecific CTLs can be induced by various immunotherapeutic strategies (reviewed in 3), and tumor-infiltrating lymphocytes are found "naturally" in tumors (6).…”
mentioning
confidence: 99%